Influence of silver additions on the structure and phase transformation of the Cu-13 wt % Al alloy - Arruda, G. J. [UNESP]; Adorno, A. T. [UNESP]; Benedetti, Assis Vicente [UNESP]; Fernandez, J.; Guilemany, J. M. (Springer Nature, 1997)
The influence of silver additions on the structure and phase transformation of the Cu-13 wt % Al alloy was studied by differential thermal analysis, X-ray diffraction, scanning electron microscopy and energy dispersive analysis of X-rays. The results indicate that the presence of silver modifies the phase-stability field, the transition temperature and the structure of the alloy. These effects are more pronounced for silver concentrations up to 8 wt %.
Keywords: Addition reactions; Annealing; Differential thermal analysis; Melting; Phase equilibria; Phase transitions; Scanning electron microscopy; Silver; Structure (composition); Thermodynamic properties; X ray diffraction; Copper aluminum silver alloy; Energy dispersive analysis of x ray; Homogenization; Phase stability field; Silver concentration; Transition temperature; Copper alloys